EXTREME LASER RADIATION: PHYSICS AND FUNDAMENTAL APPLICATIONS : Supercontinuum spectrum upon filamentation of laser pulses under conditions of strong and weak anomalous group velocity dispersion in transparent dielectrics. (31st March 2017) - Chekalin, S V; Kompanets, V O; Dormidonov, A E; Zaloznaya, E D; Kandidov, V P
Abstract: Using experiment and numerical simulation, we study the effect of anomalous group velocity dispersion (AGVD) on the formation of a visible supercontinuum band and light bullets arising in the course of filamentation of mid-IR femtosecond pulses in fused silica and fluorides. It is found that the anti-Stokes shift of the visible band increases with increasing energy of the pulse, the centre wavelength of which lies in the region of weak AGVD, and does not depend on this energy in the region of strong AGVD. A criterion is introduced for assessment of the AGVD 'strength', at which the stable visible supercontinuum band accompanies the formation of a robust light bullet in the mid-IR filament.